Peranan Perempuan Transmigran Jawa dalam Meningkatkan Ekonomi Keluarga di Nagari Sungai Duo Kecamatan Sitiung Kabupaten Dharmasraya - Fajra Adhilo Putrawera Pratama; Najmi Najmi (Jurusan Sejarah FIS UNP, 2023)
Javanese transmigrant women have experienced a paradigm shift towards the division of labor due to economic needs in fulfilling their daily lives. The lack and limitation of their husband's income, the increasing demands of life's needs encourage housewives to take the initiative to be independent and work in the public and domestic sectors. Women are always considered as domestic workers, or homemakers, who do not have the ability to actively contribute outside the home, so their role is limited to activities within the home. This study aims to determine the economy of Javanese transmigrant women in improving the family economy in Nagari Sungai Duo, Sitiung District, Dharmasraya Regency. The research method used is the historical method which consists of topic selection, heuristics, criticism, interpretation, and historiography. The findings show that the role of Javanese transmigrant women in improving the family economy in Nagari Sungai Duo is that there are three main activities that are generally carried out by the Javanese transmigrant women, such as women farming groups, farming laborers, and raising cattle. Based on the findings, it can be concluded that Javanese transmigrant women are able to play a role in meeting the economic needs of their families as additional income from their husbands.